PEMERIKSAAN KESEHATAN DASAR SISWA REMAJA NEGARA 1 MUARA BUNGO KABUPATEN BUNGO - Karlinda, Karlinda; Metriana Erza, Desi; Asmarani, Asmarani (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Adolescents face complex health problems, even though they have long been considered a healthy group. From several surveys it is known how big the problems faced by teenagers are, as can be seen from the following data: The 2007 Indonesian Demographic and Health Survey (SDKI) shows that 17% of women currently aged 45-49 years were married at the age of 15. The aim of this service is to see the influence of gender, height, weight on blood pressure and blood sugar in adolescents. The population in this study were MAN I Muara Bungo students, and the research sample was MAN I Bungo students who took part in scout extracurricular activities and took part in end-of-year camp activities. The total sample was 50 people consisting of 2 supervisors and 48 MAN I Bungo students. The results showed that there was no relationship between gender and blood sugar, gender and blood pressure, height and blood sugar, body weight and blood sugar, and body weight and blood pressure (p=0.787; p=0.158; p=0.990 ; p=0.179; p=0.470). Another thing shows that there is a relationship between height and blood pressure (p=0.009).